2015
DOI: 10.1155/2015/640234
|View full text |Cite
|
Sign up to set email alerts
|

Fuchs Endothelial Corneal Dystrophy: Strong Association with rs613872 Not Paralleled by Changes in Corneal EndothelialTCF4mRNA Level

Abstract: Fuchs endothelial corneal dystrophy (FECD) is a common corneal endotheliopathy with a complex and heterogeneous genetic background. Different variants in the TCF4 gene have been strongly associated with the development of FECD. TCF4 encodes the E2-2 transcription factor but the link between the strong susceptibility locus and disease mechanism remains elusive. Here, we confirm a strong positive association between TCF4 single nucleotide polymorphism rs613872 and FECD in Polish patients (OR = 12.95, 95% CI: 8.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…The FECD-associated expanded TGC repeat in TCF4 is also an intronic repeat. However, our differential gene expression analysis data (unpublished) and reported studies [ 28 , 43 ] have shown that expression levels of TCF4 mRNA in the corneal endothelium between FECD cases and controls and between carriers of risk and non-risk alleles of SNP rs613872 are similar indicating that transcription inhibition likely is not involved in the pathogenesis of FECD.…”
Section: Discussionmentioning
confidence: 60%
“…The FECD-associated expanded TGC repeat in TCF4 is also an intronic repeat. However, our differential gene expression analysis data (unpublished) and reported studies [ 28 , 43 ] have shown that expression levels of TCF4 mRNA in the corneal endothelium between FECD cases and controls and between carriers of risk and non-risk alleles of SNP rs613872 are similar indicating that transcription inhibition likely is not involved in the pathogenesis of FECD.…”
Section: Discussionmentioning
confidence: 60%
“…15,17 TCF4 mutations cause Pitt-Hopkins syndrome, (PTHS) 18 and TCF4 gene variants have been strongly associated with the development of Fuchs endothelial corneal dystrophy (FECD). 19 To our knowledge, there have been no reports of patients with SAK in combination with PTHS or FECD. None of the patients with SAK in this family had any symptoms related to either PTHS or FECD.…”
Section: Discussionmentioning
confidence: 96%
“…Transcription factor 4 appears to function through Wnt‐dependent and ‐independent pathways and may impact on epithelial homeostasis . TCF4 mutations cause Pitt‐Hopkins syndrome, (PTHS) and TCF4 gene variants have been strongly associated with the development of Fuchs endothelial corneal dystrophy (FECD) . To our knowledge, there have been no reports of patients with SAK in combination with PTHS or FECD.…”
Section: Discussionmentioning
confidence: 99%
“…penetrance and different degree of correlation between ethnicities. 1,28,102,104,123,138 The second most frequent cause of endothelial decompensation is pseudophakic bullous keratopathy (PBK). Despite the major advances in cataract surgery and ophthalmic viscosurgical devices, phacoemulsification can damage the endothelial layer and result in corneal decompensation.…”
Section: Common Endothelial Diseasesmentioning
confidence: 99%